2016
DOI: 10.7863/ultra.14.09040
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue Is Increased in Patients With Inflammatory Bowel Disease

Abstract: Objectives Patients with inflammatory bowel disease (IBD) have high cardiovascular morbidity, and, in general, epicardial adipose tissue thickness is related to atherosclerotic vascular disease. This study aimed to investigate the association between epicardial adipose tissue thickness and carotid intima‐media thickness as markers of early atherosclerosis in patients with IBD. Methods The study comprised 47 patients with IBD (25 with Crohn disease and 22 with ulcerative colitis) and 35 control participants. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In 23 studies with 1367 IBD patients and 1127 matched controls [ 13 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], cIMT was found to be significantly increased in patients with IBD compared with the matched controls (Cohen’s d: 0.63; 95% CI: 0.34, 0.93; p < 0.01, Figure 2 A). However, the heterogeneity among the studies was significant (I 2 = 91.84%; p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 23 studies with 1367 IBD patients and 1127 matched controls [ 13 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], cIMT was found to be significantly increased in patients with IBD compared with the matched controls (Cohen’s d: 0.63; 95% CI: 0.34, 0.93; p < 0.01, Figure 2 A). However, the heterogeneity among the studies was significant (I 2 = 91.84%; p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Participant characteristics of included studies; Table S2: Measures of disease activity and data on treatment in patients with IBD of included studies; Table S3: Outcomes of patients with IBD and Controls in included studies; Figure S1: Funnel plot of publication bias of cIMT, cfPWV, and FMD. References [ 13 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…Specifically, rheumatoid arthritis, systemic lupus erythematosus and systemic sclerosis are accompanied by an increase in epicardial fat volume that is proportional to the duration and severity of the underlying disease and is paralleled by changes in diastolic filling parameters 134–136 . Epicardial adiposity is also seen in psoriasis, 137 inflammatory bowel disease, 138 and chronic pulmonary inflammation 139 . Similarly, in obesity, epicardial adipose tissue volume is increased 140 in relation to the degree of microvascular dysfunction, cardiac fibrosis, and ventricular hypertrophy 128 and to adverse changes in diastolic filling, LA dimensions and global longitudinal strain 7,130,141 .…”
Section: Deleterious Biological Transformation Of Epicardial Adipose mentioning
confidence: 99%
“…Previous studies showed that several systemic inflammatory diseases, including rheumatoid arthritis, systemic lupus erythematosus, and psoriasis, are accompanied by an increase in EAT mass, which is proportional to the duration and severity of the underlying disease. 25–27 In SSc, increased EAT volume was also suggested to be associated with the presence and severity of the disease. 28 In particular, the activation of aldosterone, leptin, and neprilysin observed in systemic inflammatory disease may facilitate the accumulation and dysfunction of EAT.…”
Section: Discussionmentioning
confidence: 99%